Effectiveness of massage therapy injury sports methods ali satia graha: experimental study against chronic ankle - Mahesvi, Hafiz; Sukarmin, Yustinus; Suhartini, Bernadeta; Graha, Ali Satia (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. The chronic ankle injury will interfere with the range of motion of the ankle joints, such as dorsiflexion, plantarflexion, inversion, and eversion. The motion of the ankle joint will be painful and limited. However, many methods are applied instead of curing the situation. Thus, the purpose of this study was to determine the effectiveness of massage therapy for sports injuries using the Ali Satia Graha method on pain and range of motion in the ankle.Material and Methods. This study used a Pre-experimental design with a one-group Pretest-Posttest Design. The subjects in this study were determined by the perposive sampling technique, so 15 male patients aged 25"“50 years were sampled. Where patients have chronic ankle injuries. In this study, the subjects were given treatment in the form of massage therapy for sports injuries using the Ali Satia Graha method. Instruments in the study were a numeric rating scale (NRS) for pain measurement and a goniometer with units of degrees for range of motion. Analysis in this study was assisted using the SPSS version 26 application.Results. The results of the treatment of sports injuries with massage therapy by the Ali Satia Graha method on pain perception showed a significance value of 0.000 <0.05. So it can be said that there is significant effectiveness in reducing pain perception in chronic ankle pain. Furthermore, massage therapy for sports injuries using the ali satia graha method on dorsiflexion, plantarflexion, inversion, and eversion movements shows a significance value of p = 0.000 <0.05. Based on these results, it provides evidence that massage therapy for sports injuries using the Ali Satia Graha method has a significant effect on range of motion in chronic ankles.Conclusions. Based on these results, it has been established that the treatment of sports injuries with massage therapy by the Ali Satia Graha method can reduce pain perception and provide an increase in the range of motion in chronic ankle injuries.